Chile, Mining Country. Social License and Places of Enunciation in the Socioenvironmental Conflicts in Chile [Chile, País Minero. Licencia Social y Lugares de Enunciación en Los Conflictos Socioambientales en Chile] - Ortiz-Calderon, C; Broitman-Rojas, C (Ariadna Ediciones, 2021)
The discussion about “Chile, mining country” is necessary to open the debate beyond the sectorial and disciplinary vision, and to consider the need of agreements between direct and indirect stakeholders involved in the extractive activity. The visualization of the mining activity inserted in the local and regional dimensions, can help to minimize the negative impacts of the mining cycle that is framed in an extractivist model for exportation. By doing this, it will be possible to foster meeting spaces about the involved dimensions beyond the merely productive aspects. Posing a territorial planning need, recognizing different ontologies and another State participation, the stakeholders could monitor the mining activities’ performances. A mining industry that includes environmental aspects, the rights of people, communities and public opinion can be legitimized by a reformulation of the political, productive, economic and environmental culture. © 2021 Ariadna Ediciones. All rights reserved.